Investigating the English language needs of Statistical Department Students of IST AKPRIND Yogyakarta - Suprih Ambawani; Bernadetta Eko Putranti (UAD TEFL International Conference)
The objective of this study was to investigate the English language needs of Statistical Department of IST AKPRIND Yogyakarta. 50 fourth and sixth semester Statistical students, the head of the department, 2 subject specialists and 4 alumni took part in this study. Data collection tools were questionnaire and interviews guide. This study followed qualitative and quantitative method. The findings showed most students studied English for having basic communication skills needed in the workplace. The result also showed speaking and reading skills became the main focus on studying English. Those two skills had a significant effect on their academic performance in content subjects and future jobs. In addition, the most important English language sub skills were listening to lectures, performing academic presentations, reading journal articles, reading textbooks and writing summary. The problems in listening were speakers speak too fast, unfamiliar words and lack of activity using English. Problem with pronunciation was encountered in speaking. Understanding general information of the text and finding specific information were the main problems in reading. The main problems in writing were vocabulary and construct good sentences with correct grammar. The students liked discussion and presentation as teaching and evaluation method. It is hoped those findings would be the basis for designing a suitable course that meet students’ needs.